Pernikahan dalam Perspektif Islam dan Parmalim - Ardila, Syahputri (ANWARUL, 2023)
This research is entitled "Marriage in the Perspective of Islam and Parmalim". Marriage in Islam and Parmalim there are differences and similarities namely; The first is about conditions, while the same conditions are the presence of a bride and groom. Secondly regarding the marriage contract, in Islam the marriage contract is called the ijab qabul, while in the Parmalim religion it is known as the blessing. The third is regarding the dowry, which in Islam can be in the form of money, a ring, a set of prayer tools, the holy Koran, other items or recitations of the holy verses of the Koran, while in the Parmalim religion it can also be in the form of goods, money or rings, which are handed over at the time of the marriage contract. The fourth equation is witnesses from both sides of the bridegroom and bride. Fifth, regarding pre-marital, namely provision before marriage, in Islam it is known as rapak while in Parmalim religion it is known as counseling or teaching which teaches about advice before marriage. The type of research used by researchers is a type of library research. Based on this research, it is interesting to get some interesting findings, namely; knowing how the correlation of marriage in Islam and Parmalim, there are similarities regarding Islamic and Parmalim religious marriages, namely: First regarding the conditions, the same condition is that there is a bride and groom. Secondly regarding the marriage contract, in Islam the marriage contract is called the ijab qabul, while in the Parmalim religion it is known as the blessing. The third is regarding the dowry, which in Islam can be in the form of money, a ring, a prayer kit, the holy Qur'an, other items or recitation of the holy verses of the Koran, while in the Parmalim religion it can also be in the form of goods, money or the ring, which is handed over at the time of the marriage ceremony in Islam is known as rapak while in Parmalim religion it is known as guidance counseling or teaching which teaches about advice before marriage.